Motor Performance is Impaired Following Vestibular Stimulation in Ageing Mice - Tung, Victoria W. K.; Burton, Thomas J.; Quail, Stephanie L.; Mathews, Miranda A.; Camp, Aaron J. (Frontiers in Aging Neuroscience, 2016)
Balance and maintaining postural equilibrium are important during stationary and dynamic movements to prevent falls, particularly in older adults. While our sense of balance is influenced by vestibular, proprioceptive, and visual information, this study focuses primarily on the vestibular component and its age-related effects on balance. C57Bl/6J mice of ages 1, 5-6, 8-9 and 27-28 months were tested using a combination of standard (such as grip strength and rotarod) and newly-developed behavioural tests (including balance beam and walking trajectory tests with a vestibular stimulus). In the current study, we confirm a decline in fore-limb grip strength and gross motor coordination as age increases. We also show that a vestibular stimulus of low frequency (2-3 Hz) and duration can lead to age-dependent changes in balance beam performance, which was evident by increases in latency to begin walking on the beam as well as the number of times hind-feet slip from the beam. Furthermore, aged mice (27-28 months) that received continuous access to a running wheel for 4 weeks did not improve when retested. Mice of ages 1, 10, 13, and 27-28 months were also tested for changes in walking trajectory as a result of the vestibular stimulus. While no linear relationship was observed between the changes in trajectory and age, 1-month-old mice were considerably less affected than mice of ages 10, 13, and 27-28 months. Conclusion: This study confirms there are age-related declines in grip strength and gross motor coordination. We also demonstrate age-dependent changes to finer motor abilities as a result of a low frequency and duration vestibular stimulus. These changes showed that while the ability to perform the balance beam task remained intact across all ages tested, behavioural changes in task performance were observed.